Engaged Scholarship through Community Social Labs: Advancing Indigenisation of Social Work Education in Uganda (Journal of Comparative Social Work, 2025)
The indigenisation of social work education in Africa is a response to the limitations of Western-centric approaches to addressing complex local social issues. This paper explores the role of engaged scholarship and community social labs in indigenising social work education in Uganda. The study analyses data from four focus group discussions, and student WhatsApp conversations, to examine how these approaches facilitate meaningful community engagement and the integration of local knowledge into the social work curriculum. The results show that community social labs can help with cultural sensitivity and problem-solving that is relevant to the situation. They also demonstrate that institutional constraints and power dynamics may hinder this transition.Despite these issues, the study suggests that engaged scholarship through community social labs has significant potential to make social work education and practice in Uganda more culturally sensitive and responsive to local realities. Even with these challenges, the study suggests that engaging scholars in community social labs has a lot of potential to make social work education and practice in Uganda more sensitive to local cultures and needs.